STUDENT'S CONCEPTS OF AND APPROACHES TO LEARNING AND THE RELATIONSHIPS BETWEEN THEM - Mohammad Ahmad Alkhateeb; Osamah Abdel Qader Bani Milhem (LPMPP Universitas Negeri Yogyakarta, 2020)
The study attempted to characterize students’ conceptions of learning and approaches to learning and revealing the correlation between the students’ concepts and approaches to learning. The researchers used qualitative content analysis and a descriptive approach. The study population comprised 90 male and female students of the Faculty of Educational Science in the HU University, Jordan, during the 2019/2020 academic year. The quantitative concepts were dominating among students (87.77%), especially the concept of learning as a knowledge increase (33.33%). On the other hand, the qualitative concepts of learning were low (12.22%), especially on the person change (2.22%). In addition, there was an emergence of a new concept of learning outside the traditional concepts, namely learning as exam preparation. The results showed that the deep approach to learning was low, and the surface approach to learning was high. The results further showed a correlation between the quantitative concepts of learning and the surface approach to learning, as well as a correlation between the qualitative concepts of learning the deep approach to learning. Hence, the general conclusion implies that if teachers are to place learners at the heart of the learning process, they must be aware of the concepts of learning and learning approaches of the students.